Automotive Service : Inspection, maintenance, repair - Gilles, Tim (Boston Cengage Learning, 2016)
Book helps you develop the knowledge and skills you need for career success. Known for its clear explanations and high quality art, the book includes step-by-step procedures for trouble-shooting and repair.
Includes glossary and index.
Keywords: Công nghệ kỹ thuật ô tô